Modernization of management technology of economic development city on the principles of management - Monastyrskyi, Grygiriy (Skhid, 2013)
The article presents results of theoretical, methodological and practical approaches to the concept of modernization of technology economic development of the city. Substantiates the priority consideration of how economic systems, economic development which is subject to influence business management different hierarchical levels. Proved feasibility of using technological concept of economic development of the city, which involves the application of economic instruments of municipal management